An analysis of elementary students’ differential comprehension of fiction texts from barrett’s perspective - Yahya, Ayyas; Karsono, Karsono; 'Azizah, Naeliyatun (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2025)
This study examines the levels of fiction text comprehension among fourth-grade primary school students in Surakarta, Indonesia, using Barrett’s Taxonomy as the analytical framework. A descriptive qualitative approach with a case study design was employed, and data were collected through reading comprehension tests, classroom observations, and interviews with students and teachers. The five levels of comprehension literal, reorganization, inferential, evaluative, and appreciative were assessed to map the range of students’ reading abilities. The findings show notable variation across comprehension levels. Literal comprehension achieved the highest score (91.35%, high category), indicating strong ability to recall explicit information. In contrast, reorganization (40.73%) and inferential comprehension (43.20%) were categorized as low, suggesting difficulties in synthesizing information and interpreting implicit meaning. Evaluative comprehension was moderate (69.13%), while appreciative comprehension received the lowest score (35.79%), reflecting limited engagement with the emotional and aesthetic qualities of the text. Overall, the results indicate that although students demonstrate strong surface-level understanding, their higher-order cognitive and affective comprehension skills are underdeveloped. The study recommends instructional practices that extend beyond factual recall by fostering critical interpretation, reflective judgment, and deeper engagement with literary texts. The implications for curriculum design and classroom instruction are outlined to address these specific gaps in comprehension.